1995
DOI: 10.1007/bf01682034
|View full text |Cite
|
Sign up to set email alerts
|

Risks of rhG-CSF treatment in drug-induced agranulocytosis

Abstract: Nine patients with drug-induced agranulocytosis received recombinant human granulocyte colony-stimulating factor (rhG-CSF) to accelerate myeloid recovery because of life-threatening infections related to neutropenia. All patients showed a quick recovery of their granulocyte counts. Side effects were substantial, however. Three patients, two with a severe infection and one with preexisting pulmonary infiltrates, developed worsening of their respiratory status during neutrophil recovery, resulting in clinical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Since that time, others have reported similar findings [9,10,12,13,14], including several studies that have assessed risk of WRS in critically ill patients [9,12,14]. For example, up to half of critically ill cancer patients with NR experience WRS [1,12].…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Since that time, others have reported similar findings [9,10,12,13,14], including several studies that have assessed risk of WRS in critically ill patients [9,12,14]. For example, up to half of critically ill cancer patients with NR experience WRS [1,12].…”
Section: Discussionsupporting
confidence: 51%
“…Of interest, WRS has been associated with increased lung microvascular permeability in one of the reported patients [8]. Moreover, Demuynck et al [13] emphasized that preexisting lung injury or severe infection was observed in each of their patients. Our study suggests that up to one third of hematology patients with an expected neutropenia duration of more than 7 days experience this event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations